Investigando os mecanismos da circulação sanguínea em seus aspectos físicos e morfológicos - Maximiliano Martins de Souza (2020)
Teaching the circulatory system in high school can present a lot of gaps that are not easily answered by current practices used in the classroom. Methodologies addressing this topic have been discussed by several authors who point out the persistence of mistakes since elementary school till higher education, mostly related to the morphological and physical aspects that influence the blood flow. Understanding how this system works, based on hemodynamics, allows an integrated view of the central role in homeostasis, where physics, chemistry and mathematics give biological meaning to universal laws; and contemplates the integration of the Natural Sciences as proposed by the new high school model of BNCC. The present work focuses on how inquiring can promote learning of physical and morphological concepts related to regulation and control of blood flow. The Inquiry Teaching Sequence (ITS) developed focuses on the physical and morphophysiological mechanisms that control the blood circulation through the application of 3 practical activities: Simulating cardiac movements, measuring blood pressure under different conditions, and building a model for the circulatory system. The sequence emphasizes the following aspects: cardiac pumping as a source of energy for blood circulation, the unidirectional blood flow, the physical factors that influence the differences in blood pressure in the body and the circulatory pattern formed by two large loops, namely the systemic and pulmonary cycles. The work was performed by students in the 2nd year of high school and the analysis of this work was evaluated comparing previous and final versions of conceptual maps. The results showed an improvement in the production of the participating groups, thus reaching the proposed knowledge related to morphology and the influence of physical dimensions on our body. We conclude that high school students are able to understand some important aspects of the circulatory system involving interdisciplinary concepts through the application of a set of investigations and practices that promote a transformation of pre-existing concepts to a better and more consistent view.